Intestinal obstruction due to giant gastric trichobezoar: Bibliographic Review Regarding a Case (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2021)
The tricobezoar is a rare gastric tumor formation is composed of hair and affects females at a greater rate.This rare condition is associated with psychological disorders such as trichotillomania and causing intestinal obstruction. The diagnosis is based on data from the history and physical examination to find epigastric tumor mass without morbid history.Treatment is determined by the size of the mass and thus present complications surgical removal was choice in this case.Psychological assessment in this patient needed to avoid recurrences by trichophagia they present.
Keywords: intestinal obstruction; gastric tricobezoar; trichotillomania